GPU accelerated PIC and SIC for OFDM-NOMA - Manglayev, Talgat; Kizilirmak, Refik Caglar; Abdul Hamid, Nor Asilah Wati (MDPI, 2019)
Non-orthogonal multiple access (NOMA) is a candidate multiple access scheme for the fifth-generation (5G) cellular networks. In NOMA systems, all users operate at the same frequency and time, which poses a challenge in the decoding process at the receiver side. In this work, the two most popular receiver structures, successive interference cancellation (SIC) and parallel interference cancellation (PIC) receivers, for NOMA reverse channel are implemented on a graphics processing unit (GPU) and compared. Orthogonal frequency division multiplexing (OFDM) is considered. The high computational complexity of interference cancellation receivers undermines the potential deployment of NOMA systems. GPU acceleration, however, challenges this weakness, and our numerical results show speedups of about from 75–220-times as compared to a multi-thread implementation on a central processing unit (CPU). SIC and PIC multi-thread execution time on different platforms reveals the potential of GPU in wireless communications. Furthermore, the successful decoding rates of the SIC and PIC are evaluated and compared in terms of bit error rate.